1996
DOI: 10.1111/j.1476-5381.1996.tb15719.x
|View full text |Cite
|
Sign up to set email alerts
|

VIP‐ and PACAP‐mediated nonadrenergic, noncholinergic inhibition in longitudinal muscle of rat distal colon: involvement of activation of charybdotoxin‐ and apamin‐sensitive K+ channels

Abstract: 1 The mediators of nonadrenergic, noncholinergic (NANC) inhibitory responses in longitudinal muscle of rat distal colon were studied.2 An antagonist of pituitary adenylate cyclase activating peptide (PACAP) receptors, PACAP638, concentration-dependently inhibited the rapid relaxation of the longitudinal muscle induced by electrical field stimulation (EFS), resulting in a maximal inhibition of 47% at 3 MM.3 PACAP638 inhibited the relaxation by 75% in the presence of the vasoactive intestinal peptide (VIP) recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 45 publications
8
81
2
Order By: Relevance
“…On the other hand, although VIP and PACAP were suggested to separately, partially mediate NANC relaxation of the distal colon in our previous study [15], participation of both the peptides was not shown in the remaining intestinal regions in the present study (n=3).…”
Section: Mediators Of Nanc Relaxation Of Longitudinal Muscle Of Variomentioning
confidence: 47%
See 4 more Smart Citations
“…On the other hand, although VIP and PACAP were suggested to separately, partially mediate NANC relaxation of the distal colon in our previous study [15], participation of both the peptides was not shown in the remaining intestinal regions in the present study (n=3).…”
Section: Mediators Of Nanc Relaxation Of Longitudinal Muscle Of Variomentioning
confidence: 47%
“…However, the VIP receptor antagonist inhibited the relaxation in the distal colon by 36.4 ± 3.4% (n=14). Charybdotoxin at 100 nM, which exhibited the maximal inhibitory effect on EFSinduced relaxation of the Wistar-ST rat distal colon [15], also inhibited the relaxation by 37.2 ± 5.1% (n=3).…”
Section: Mediators Of Nanc Relaxation Of Longitudinal Muscle Of Variomentioning
confidence: 99%
See 3 more Smart Citations